Analysis of the nutritional composition of the flesh of the fruit of Annona senegalensis harvested in the peri-urban savannas of Brazzaville: A republic of Congo - Bopoundza, Feueltgaldah Christian; Ngwasso, Osbine Michelle Mayima; Bassiloua, Jean Bruno; Binaki, Anicet Frederic; Silou, Thomas (Journal of Food Technology Research, 2025)
Annona senegalensis, a spontaneous shrub native to tropical Africa, remains underexploited regarding its food potential, despite being part of a natural resource class whose significance is well established. The limited studies available in the literature on the nutritional value of its fruit present contradictory results. The present study aims to evaluate the nutritional composition of the flesh of fruits harvested in the peri-urban savannas of Brazzaville, revealing variability between sites: fruits from the Mabenga site exhibit higher concentrations of macronutrients than those from Lifoula, particularly in lipids (7.18% vs 4.03%) and proteins (4.28% vs 0.70%), due to a lower water content. Carbohydrate contents (26.29% vs 16.55%) are consistent with bibliographic data, while ash content remains relatively low (1.11% vs 0.61%). In terms of energy, Mabenga fruits reach 148.33 kcal/100g compared to 92.33 kcal/100g at Lifoula, positioning this species above many cultivated or foraged fruits of tropical Africa. However, these values are still lower than those of fruits rich in fats or dry, such as safou, avocado, baobab, or néré. The mineral composition is homogeneous between the two sites and generally higher than the values reported in the literature for Annona senegalensis. These findings underscore the underutilized nutritional potential of the fruit within the context of local resource valorization.